Advances in Radiotherapy in the Treatment of Metastatic Spinal Lesions - Coimbra, Brian Guilherme Monteiro Marta; Silva, Alice Roxo Nobre de Souza e; Soares, Cauã Bhering; Figueiredo, Caio César Nogueira de; Macamo, Manuel Salvado; Cristante, Alexandre Fogaça (Revista Brasileira de Ortopedia, 2025)
Metastatic spinal disease has become increasingly common due to advances in systemic oncological therapies and the increase in the overall survival of cancer patients. Its treatment is palliative, but the meaning of this term has evolved and, today, consists of better and more effective condition control over longer periods. In the past, surgical and radiotherapy techniques, especially conventional external beam radiation therapy (cEBRT), were ineffective or morbid for controlling many types of tumors. Now, the emergence and advancement of stereotactic body radiation therapy (SBRT) drastically changed this scenario. Surgery for managing metastatic disease remains significant in radiotherapy-associated strategies, but its purpose and technique have undergone major updates. However, despite all technical advances, radiotherapy has toxicity and side effects that warrant consideration. In this article, we provide an updated review covering everything from history to innovations in treating spinal metastases, focusing on their benefits, indications, and clinical impact.
Keywords: neoplasm metastasis; radiotherapy; spine/surgery